The Conditional Contribution Mechanism for the Provision of Public Goods - Andreas Reischmann (University of Heidelberg, Department of Economics, 2015)
Many mechanisms have been designed to solve the free-rider problem in public good environments. The designers of those mechanisms focused on good static equilibrium properties. In this paper, I propose a new mechanism for the provision of public goods that has good dynamic properties instead. The mechanism gives all agents the possibility to condition their contribution on the total level of contribution provided by all agents. Under a reasonable variant of Better Response Dynamics all equilibrium outcomes are Pareto efficient. This makes the mechanism particularly suited for repeated public good environments. In contrast to many previously suggested mechanisms, it does further not require an institution that has the power to enforce participation and/or transfer payments. Neither does it use any knowledge of agents preferences.
urn:nbn:de:bsz:16-heidok-184835
Keywords: 330; Mechanism Design; Public Goods; Better Response Dynamics